From Darkness to Light Writers in Museums 1798-1898 - Manthorne, Katherine (Open Book Publishers, 2019)
"From Darkness to Light explores from a variety of angles the subject of museum lighting in exhibition spaces in America, Japan, and Western Europe throughout the nineteenth and twentieth centuries. Written by an array of international experts, these collected essays gather perspectives from a diverse range of cultural sensibilities. From sensitive discussions of Tintoretto's unique approach to the play of light and darkness as exhibited in the Scuola Grande di San Rocco in Venice, to the development of museum lighting as part of Japanese artistic self-fashioning, via the story of an epic American painting on tour, museum illumination in the work of Henry James, and lighting alterations at Chatsworth (to name only a few topics) this book is a treasure trove of illuminating contributions. The collection is at once a refreshing insight for the enthusiastic museum-goer, who is brought to an awareness of the exhibit in its immediate environment, and a wide-ranging scholarly compendium for the professional who seeks to proceed in their academic or curatorial work with a more enlightened sense of the lighted space. "